Depression among nursing students associated to their self-esteem, health perception and interest in mental health (Revista Latino-Americana de Enfermagem, 2008)
This study aimed to identify the presence of depression among nursing students in relation to their self-esteem, perception of physical health and interest in mental health. METHODOLOGY: the research was carried out in class among 224 nursing students. The Depression Knowledge and Points of View questionnaire was used, as well as Beck's inventory, the Self-esteem scale and information about health and quality of life. Sociodemographic and clinical data were investigated, as well as the students' interest in mental health. The project was approved by the Ethics Committee. RESULTS: depression is present among nursing students at levels expected for the population. The statistically assessed results evidenced a correlation between physical health perception (bad and medium), interest and attendance to courses in the field, concluding that there are greater chances of depression among nursing students.